Analisis maraknya judi online di Masyarakat - Jadidah, Ines Tasya; Lestari , Utami Milyarta; Smanah Fatiha, Keysha Alea; Riyani, Roja; Neli; Wulandari, Cherrysa Ariesty (Jurnal Ilmu Sosial dan Budaya Indonesia, 2023)
Currently, the reality of a lifestyle that tends to be consumptive, especially coupled with the increasing prices of basic daily necessities due to the very fast rate of economic inflation, makes everyone want to achieve everything in a practical and instant way or according to them easily. things to do include gambling. Gambling is a criminal act, namely risking a certain amount of money where the party who wins will get the entire bet. Gambling can also be referred to as a matter of chance, gambling can be detrimental to society and the nation's moral values. This crime also causes public order, peace and security to be disturbed. Apart from that, the influence of gambling not only affects adults, but the impact of gambling also has an effect on children.